The relationship between the performance of educational administrators and organisational health with a focus on teachers' perception in high schools - Rajab, Masoumeh Pour; Basri, Ramli; Mohd Daud, Shaffe (Universiti Putra Malaysia Press, 2013)
This correlation study was aimed at determining the relationship between the performance of educational administrators and organisational health in high schools in Tehran, Iran. Cluster sampling method was used and the responses of a total of 180 teachers were obtained. Two selected questionnaires were used: the school organisational health questionnaire and the administrator performance questionnaire. The research data were analysed using SPSS software. Inferential and descriptive statistics were used: the variables were the Pearson correlation coefficient, coefficient of determination and t-test. The results of the study show that about two thirds of the schools that were studied enjoyed a high level of organisational health, and the teachers of about 30% of the schools believed that they had principals whose performance in different areas was weak. The results showed that there was a positive relationship between organisational health and the performance of the principals. The findings also indicated a relationship between administrator performance in the areas of education and the teaching programme, student affairs and staff affairs and organisational health.